Implikasi spasial kegiatan bertinggal rumah tangga extended berlandaskan nilai sosio-kultural kekerabatan di Balikpapan, Indonesia - Wendy I. Hakim; Triatno Y. Harjono; Dalhar Susanto (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
There is a recent focus on households as residential units but most of the studies conducted rely on demographic and economic perspectives using economic value maximization schemes. The research on the household is considered necessary due to its close relation to family and kinship issues observed in different aspects of life and based on societal diversity associated with certain socio-cultural values. This is most important in Asia, including Indonesia, where extended families and households are regarded as ideal. Therefore, this study was conducted to understand the significance of socio-cultural values ​​on the spatial living implications in extended households using qualitative methods, especially ethnography, which involved targeted informants, interviews, and observations. The results showed that the socio-cultural values ​​held by the members of the household are based on the definition of kinship as a valuable bond, desire to share, cooperation, as well as the acceptance and sustenance of tradition. Moreover, the spatial arrangement concerning the allocation, use, and access to rooms based on gender in an extended family was observed to be identical to those in a nuclear family. Meanwhile, additional members are allowed to use different rooms in the house and also to interact with hosts.